(3JQTjM GdEOQGc aj JTQjM GdCadGcs - (3EHQGgje Hf MjOQ Hf CMeO GdcQOi GdUahi GdMSjf BHGOi GdTGaYjs; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s ((3Wg Hf ehSi Hf YHjO Gddg GdMSjfi GdcQeGfi s)
(3ChdgG (B:s
(3Gddge jG cQje hHYO , ajbhd HgGA GdOjf gPg OQI jJjeI , hjbhd EHQGgje Hf MjOQ CQOJ Gf CTQMgG aCSdcgG HPdc ai MdbI PgHjI ef cd YjH dCfgG bO EMJhJ SQ af GdgjFI s
(3BNQgG (B:s
(3Ef cGfJ MceI Yfg , jfUH ebjGS GdEbdje Ydi SWM GdCQV , aSeJ GdXd SGYJFP jchf SeJ GdbHdI , bO hbY GdaQGZ ef gPG GdTQM GdehShe SfI SHY hCQHYjf heFI hCda Je s
(3HgG QShes
(3cJHgG GdfGSN ef fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
Keywords: (3Gdadcs